2016
DOI: 10.4236/as.2016.712079
|View full text |Cite
|
Sign up to set email alerts
|

Covering Rearing Tanks Improves Brown Trout Growth and Feed Conversion

Abstract: Although an important part of the natural environment of fish, overhead cover is usually absent during hatchery rearing. To evaluate the possible influence of overhead cover on juvenile brown trout Salmo trutta hatchery rearing performance, this study compared three different cover treatments: near-full (98%) cover, partial (65%) cover, and no cover (completely open). After 12 weeks of rearing in 1.8 m-diameter circular tanks, total tank weight gain was significantly greater and feed conversion ratios were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous studies showed that overhead covers providing shade and visual isolation could be beneficial to fish performance in salmonids [11,12]. We hypothesized that immersed covers could provide the same benefits, and at the same time provide better shelter and a higher environmental complexity to the reared fish.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies showed that overhead covers providing shade and visual isolation could be beneficial to fish performance in salmonids [11,12]. We hypothesized that immersed covers could provide the same benefits, and at the same time provide better shelter and a higher environmental complexity to the reared fish.…”
Section: Introductionmentioning
confidence: 93%